Cat memoir jako forma pisarstwa (auto)biograficznego - Szalewska, Katarzyna (Zagadnienia Rodzajów Literackich, 2021)
The article is an attempt to analyze a specific form of autobiographical writing, which is pet memoir, and in particular — cat memoir. The author, inspired by the works of Éric Baratay, asks questions about the ways in which animal biographies are constructed. Then these reflections are applied to the book Iwan Konwicki, z domu Iwaszkiewicz by Tadeusz Konwicki. Animal biographies are a difficult genre that generates numerous methodological problems, which, moreover, it shares with other directions of reflection developed during animal studies. However, what is expressed by attempts to create these type of descriptions (doomed to failure in the dimension of adopting the full zoocentric perspective) is the restoration of the animal to history. This peculiar historicization of non-human subjects means not only restoring their individualism and agency, but also supplementing the traditional narrative about the past with a previously neglected dimension. The article consists of a theoretical part in which the author recalls the most important concepts related to pet memoirs as a genre of autobiographical writing and examples of its implementation, and an interpretative part concerning Konwicki’s book, in which Ivan… is read with reference to the conventions of traditional biography and the idea of a biography of associated species. As part of the reflection presented in the article, issues such as: animal agency, the role of animals in culture, the animal point of view, anthropomorphization, zoocentric narratives will be taken up.